The Influence of Leadership Innovation and Collaboration on the Performance of West Sumatra Provincial Health Service ASN - Afando Ekardo; Cashtry Meher; Ahyar Wahyudi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The performance of civil servants is needed in a government agency to improve performance. Therefore, to make it happen, skilled and reliable human resources are needed in their fields. Innovation in the field of public services is needed for the creation of comfortable public services. Collaborative leadership is needed to cope with rapid change. The purpose of this study is to determine the Influence of Innovation and Leadership Collaboration on the Performance of ASN of the West Sumatra Provincial Health Office. The qualitative research method uses a descriptive approach, where the data collected is in the form of interview manuscripts, field notes, and other official documents. The results of innovation show that the form of public service